Historical Nihilism and Science Fiction in the New Russian and Lithuanian Neo-Pagan / Patriotic Movements - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2010)
In this study, some alternative new religious / national / racial identity construction cases have been analyzed in order to reveal the mechanism of contemporary alternative religious / ethnic / racial identity construction. It was found that this mechanism works in two axes – 1) historical nihilism (which in this study is defined as rejection of professional history, scientifically constructed vision of national / religious history), and 2) fiction, which manifests itself as an individual or a collective creation of new myths, historical fictions, which are presented as the true history which has been forgotten and distorted by various enemies (Christians, Jews, Europeans, and so on). In the study has been presented an analysis of the movement of growing popularity both in Russia and beyond, including Lithuania, of Rodnovers (slavic-arian neopagans) and created on the basis of teachings of leading authorities of this movement – A. Trehlebov and A. Hinevitch, – “publicistic” movie of Sergei Strizhak “Games of the Gods”. Another example was the famous Russian mathematician topologist Fomenko and his new method of chronology, resulting in other historical fiction. In the study was also discussed question of the fake of one of the main sources of Rodnovers – Book of Veles. In this study, the areas of the influence of this Russian movement in Lithuania and similar efforts toward the new constructions of Lithuanian identity have also been found. Here are single cases of admiration of teachings of Trehlebov and Hinevitch, Lithuanian branch of another Russian movement, CNS (Conception of National Security), in which there are some traces of teachings of Rodnovers, and the most important – the most recent movement of Sarmatia. Analysis of this movement shows a fundamental difference between Rodnovers and “Sarmatians”, that the latter, although utilize many fantasies, but is not dismissing the science of history as such, but causes discontent and criticism of professional historians (or their indifference), requesting them to take seriously the sources they designate to in order to restore the historical memory and Lithuanian identity, which, according to representatives of this movement are deliberately discouraging and falsifying this identity by existing official “experts” of Lithuanian national identity.